The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1111/ntwe.12140
|View full text |Cite
|
Sign up to set email alerts
|

Online privacy in job recruitment processes? Boundary work among cybervetting recruiters

Abstract: This article addresses various ways that cybervetting recruiters (re)construct boundaries around the public–private division. Based on interviews with 37 recruiters in Sweden, we show how the practice of cybervetting is legitimised by the recruiters’ descriptions and accounts in relation to various notions of privacy and norms of information flow. We present this as a boundary work aided by especially two ways of framing information: the repertoire about accessible information and the repertoire of relevant in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(34 citation statements)
references
References 32 publications
1
30
0
Order By: Relevance
“…Although there are now trends in legislation inhibiting organizations from requesting applicants' social media passwords to conduct screening, there is nothing preventing them from vetting whatever is available for the public to see (Davison et al, 2016; Kluemper, Davison, Cao, & Wu, 2015). In fact, a recent study of hiring managers revealed that they generally believe any personal information on the internet can be used to inform decisions, because the applicant has chosen not to keep that information private (Backman & Hedenus, 2019). However, this is a double‐edged sword for applicants because not posting “enough” information can be viewed as the applicant having something to hide or signaling a lack of technology‐related competency (e.g., Carr, 2016).…”
Section: Applicant Atcmentioning
confidence: 99%
See 1 more Smart Citation
“…Although there are now trends in legislation inhibiting organizations from requesting applicants' social media passwords to conduct screening, there is nothing preventing them from vetting whatever is available for the public to see (Davison et al, 2016; Kluemper, Davison, Cao, & Wu, 2015). In fact, a recent study of hiring managers revealed that they generally believe any personal information on the internet can be used to inform decisions, because the applicant has chosen not to keep that information private (Backman & Hedenus, 2019). However, this is a double‐edged sword for applicants because not posting “enough” information can be viewed as the applicant having something to hide or signaling a lack of technology‐related competency (e.g., Carr, 2016).…”
Section: Applicant Atcmentioning
confidence: 99%
“…Although similar recommendations have been made for cybervetting, the practice is largely unstandardized (e.g., Davison et al, 2016; Roth, Bobko, Van Iddekinge, & Thatcher, 2016) similar to unstructured interviews and resumé evaluation (Gatewood et al, 2008; Highhouse, 2002). One hiring manager who is screening an applicant's profile without any established criteria can have completely different perceptions compared to another manager assessing the same applicant but using their own criteria (Backman & Hedenus, 2019). This lack of standardization prevents consistent, reliable, and valid screening of an applicant's social media profile.…”
Section: Applicant Atcmentioning
confidence: 99%
“…Importantly, these informational norms should not be considered as fixed and static; rather, they are time sensitive and vary across points in time and between cultures, locations and societies [ 1 ]. The Contextual Integrity framework has been used across numerous contexts, ranging from dataflows in smartphone usage [ 22 , 23 ], education [ 24 , 25 ], healthcare [ 26 ] and even recruitment [ 27 ].…”
Section: Theoretical Considerationsmentioning
confidence: 99%
“…The popular press [2], practitioner [3,4] and scholar literature [5,6,7] confirm that this practice is becoming widespread. However, the use of this source of information in personnel selection is replete with dangers, including those associated with violations of privacy and laws, discrimination, lack of reliability and validity [8,9,10,11,12,13].…”
Section: Introductionmentioning
confidence: 99%